Public Trust in Sidoarjo After The Corruption Case Gus Muhdlor is Facing in 2024 - Albert E. Barona; Mutiara Ramadhani Putri Rismawan (Journal of Religion, Local Politics, and Law, 2025)
This corruption that ensnared Sidoarjo's regent, Gus Muhdlor, as 2024 drew a public trust crisis over local leadership. The issue is important because public trust is the foundation of local democratic legitimacy. The study aims to examine the effect that cases of corruption have on public trust and the political participation of Sidoarjo residents. A qualitative approach is used through in-depth interviews and analysis of social media commentary. Research shows an increasing skepticism of people's politics, but it does not yield to total apathy. Instead, active citizens form political discontent in digital space, signifying a shift in trust from leadership figures to community collectivity. In conclusion, though the leadership figure loses credibility, the political consciousness of people remains high. The study recommends more open public communication reform and digital space use as a platform for constructive participation in local democracy.